ANALISIS POLA KESULITAN BELAJAR MATEMATIKA DALAM MENYELESAIKAN SOAL OPERASI HITUNG PECAHAN PADA SISWA SEKOLAH DASAR - Ilham Arief Nugroho; Imaniar Purbasari; Ahmad Bakhruddin (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2023)
The main problem to be studied in this research is analyzing the pattern of mathematics learning difficulties when solving fraction calculation problems for elementary school students. This research aims to gain an in-depth understanding of the pattern of difficulties students face when understanding and answering fraction calculation questions. This study aims to analyze the pattern of mathematics learning difficulties of elementary school students when completing fraction calculation operations. The sample includes 5 subjects consisting of 5th grade students at SD Negeri 4 Mayonglor Jepara. Data collection was carried out through observation, as well as interviews with students and teachers. The data will be analyzed and used to explain the problem being studied. The results of data analysis show that students experience various difficulties in understanding the basic concepts of fractions and the ability to calculate fractions. One of the biggest difficulties is understanding the relationship between the numerator and denominator of a fraction. Students also often have difficulty converting fractions into their simplest form, changing fractions from mixed fractions to improper fractions and vice versa. Apart from that, understanding fractions with different denominators is also a challenge for students. The conclusion of this research is that elementary school students face many different difficulties when solving fraction calculation problems. These difficulties include understanding the basic concepts of fractions, changing the form of fractions, calculating the results of multiplying or dividing fractions, simplifying fractions, and applying fractions in the context of everyday situations